Association of MTRR A66G polymorphism (but not of MTHFR C677T and A1298C, MTR A2756G, TCN C776G) with homocysteine and coronary artery disease in the French population - Guéant-Rodriguez, Rosa-Maria; Juilliére, Yves; Candito, Mirande; Adjalla, Charles E.; Gibelin, Pierre; Herbeth, Bernard; Obberghen, Emmanuel Van; Guéant, Jean-Louis (Thrombosis and Haemostasis, 2005)
methylenetetrahydrofolate reductase polymorphism (MTHFR C677T) is an established determinant of homocysteine plasma level (t-Hcys) while its association with coronary artery disease (CAD) seems to be more limited. In contrast, the association of the substitutions A2756G of methionine synthase (MTR), A66G of methionine synthase reductase (MTRR) and C776G of transcobalamin (TCN) to both t-Hcys and CAD needs to be evaluated further. The objective was to evaluate the association of these polymorphisms with t-Hcys and CAD in a French population. We investigated the individual and combined effects of these polymorphisms and of vitamin B12 and folates with t-Hcys in 530 CAD patients and 248 matched healthy controls. t-Hcys was higher in the CAD group than in controls (11.8 vs 10.4 μM, P<0.0001) and in carriers of MTRR AA and MTHFR 677TT than in those carrying the most frequent allele of both polymorphisms (13.8 vs 11.4 μM, P=0.0102 and 12.5 vs 11.0 mM, P=0.0065 respectively). The frequency of MTRR A allele was higher in CAD patients than in controls (0.48 [95% CI: 0.44-0.52] vs 0.38 [95% CI: 0.32-0.44], P=0.0081) while no difference was observed for MTHFR 677T frequency. In multivariate analysis, t-Hcys > median and MTRR AA genotype were two significant independent predictors of CAD with respective odds ratios of 3.1 (95 % CI: 1.8-5.1, P<0.0001) and 4.5 (95% CI: 1.5-13.1, P=0.0051). In conclusion, in contrast to North Europe studies, MTRR AA genotype is a genetic determinant of moderate hyperhomocysteinemia associated with CAD in a French population without vitamin fortification.
Keywords: Coronary artery disease; folate; homocysteine; methionine synthase reductase; transcobalamin; vitamin B12